2016
DOI: 10.1186/s13195-016-0216-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes measures in a decade of dementia and mild cognitive impairment trials

Abstract: BackgroundIn a research study, to give a comprehensive evaluation of the impact of interventions, the outcome measures should reflect the lived experience of the condition. In dementia studies, this necessitates the use of outcome measures which capture the range of disease effects, not limited to cognitive functioning. In particular, assessing the functional impact of cognitive impairment is recommended by regulatory authorities, but there is no consensus on the optimal approach for outcome assessment in deme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
92
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 23 publications
2
92
0
2
Order By: Relevance
“…Moreover, although several reviews reported meta-analytic results for subjective cognition, psychosocial and functional outcomes, the pooled effect estimates were generally based on a small number of primary trials and, within these broad categories, a diverse set of outcomes and instruments had been employed. The fact that clinically relevant outcomes are assessed infrequently and with heterogeneous measures has previously been highlighted (Harrison, Noel-Storr, Demeyere, Reynish, & Quinn, 2016;Lees, Fearon, Harrison, Broomfield, & Quinn, 2012) and attempts have been made to increase harmonisation (Webster et al, 2017), which seems imperative in order to improve synthesis efforts in the field of cognition-oriented treatments.…”
Section: Overall Completeness Of the Evidencementioning
confidence: 99%
“…Moreover, although several reviews reported meta-analytic results for subjective cognition, psychosocial and functional outcomes, the pooled effect estimates were generally based on a small number of primary trials and, within these broad categories, a diverse set of outcomes and instruments had been employed. The fact that clinically relevant outcomes are assessed infrequently and with heterogeneous measures has previously been highlighted (Harrison, Noel-Storr, Demeyere, Reynish, & Quinn, 2016;Lees, Fearon, Harrison, Broomfield, & Quinn, 2012) and attempts have been made to increase harmonisation (Webster et al, 2017), which seems imperative in order to improve synthesis efforts in the field of cognition-oriented treatments.…”
Section: Overall Completeness Of the Evidencementioning
confidence: 99%
“…Work is underway to establish a core outcome set for evaluating non‐pharmacological interventions for people living at home with dementia . In the context of the development of pharmaceutical interventions, it is widely argued that better testing of clinical meaningfulness and the lived experience of individual patients is essential in AD clinical trials …”
Section: Introductionmentioning
confidence: 99%
“…The first challenge in drug development in AD is that there is no consensus on the optimal approach for outcome assessment in dementia research, particularly within the preventative paradigm at the earlier stage of the disease course. A literature review by the authors concluded there are currently no validated PROMs used in the AD clinical trials for the early (pre‐clinical) stage of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Although HRQoL is one of the main measures used to evaluate health outcomes and several questionnaires are available for assessing HRQoL in people with dementia at different stages of disease progression, very few instruments designed specifically to appraise people with MCI are available (Bowling et al, 2015; Dichter, Schwab, Meyer, Bartholomeyczik, & Halek, 2016; Yang, Dawes, Leroi, & Gannon, 2018). In general, the instruments used to assess HRQoL or other patient‐reported health outcomes require the respondent to demonstrate adequate cognitive performance (Harrison, Noel‐Storr, Demeyere, Reynish, & Quinn, 2016). In many cases, these instruments are long and very complex (e.g., in terms of the number of response alternatives provided), which makes them difficult to use for people with MCI.…”
Section: Introductionmentioning
confidence: 99%